2017
DOI: 10.3389/fimmu.2017.00130
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Murine Natural Killer Cell Development

Abstract: Natural killer (NK) cells are effector lymphocytes of the innate immune system that are known for their ability to kill transformed and virus-infected cells. NK cells originate from hematopoietic stem cells in the bone marrow, and studies on mouse models have revealed that NK cell development is a complex, yet tightly regulated process, which is dependent on both intrinsic and extrinsic factors. The development of NK cells can be broadly categorized into two phases: lineage commitment and maturation. Efforts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 80 publications
1
60
0
Order By: Relevance
“…In mice, commonly used surface markers to identify NK cells are NKp46, CD49b (DX5), and CD161 (NK1.1) gated on CD3-negative cells. In some mouse strains, such as BALB/c, NK cells are identified only by CD49b and NKp46, as these strains have allelic variants of the NK1.1 and do not react with the anti-NK1.1 antibody PK136 (36)(37)(38)(39). In contrast to human NK cells, the surface density of CD27 and CD11b can be used to subdivide murine NK cells into four subsets that define different levels of maturation: CD11b low CD27 low , CD11b low CD27 high , CD11b high CD27 high , and CD11b high CD27 low (40,41).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, commonly used surface markers to identify NK cells are NKp46, CD49b (DX5), and CD161 (NK1.1) gated on CD3-negative cells. In some mouse strains, such as BALB/c, NK cells are identified only by CD49b and NKp46, as these strains have allelic variants of the NK1.1 and do not react with the anti-NK1.1 antibody PK136 (36)(37)(38)(39). In contrast to human NK cells, the surface density of CD27 and CD11b can be used to subdivide murine NK cells into four subsets that define different levels of maturation: CD11b low CD27 low , CD11b low CD27 high , CD11b high CD27 high , and CD11b high CD27 low (40,41).…”
Section: Introductionmentioning
confidence: 99%
“…1a). Within the lineagenegative NK1.1 + compartment, we defined CD11bcells as immature (iNK) cells, further subdividing the CD11b + mature (mNK) compartment by their expression of CD27 into a CD27 + subset of intermediate maturity, which for simplicity is sometimes called "mNK1", and a more mature CD27subset called "mNK2" (Kim et al, 2002;Chiossone et al, 2009;Goh and Huntington, 2017). Eomes -CD49a + cells, suggested to represent ILC1, have previously been reported within the Lineage-negative NK1.1+ bone marrow compartment (Klose et al, 2014), although other studies have failed to find a prominent ILC1 population within this gate (Turchinovich et al, 2018;Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…NK cells are considered innate immune cells since they express germline-encoded antigen receptors and their development does not need RAG expression or V(D)J recombination [55-58]. Paradoxically, NK cells often have V(D)J rearrangements at AgR loci and RAG reporters showed that ∼40% of NK cells develop from RAG-expressing common lymphoid precursors [59-63].…”
Section: Rag Dna Cleavage Regulates Development and Function Of Innatmentioning
confidence: 99%